2008
DOI: 10.1371/journal.pone.0003507
|View full text |Cite
|
Sign up to set email alerts
|

Active Transport of the Ubiquitin Ligase MID1 along the Microtubules Is Regulated by Protein Phosphatase 2A

Abstract: Mutations in the MID1 protein have been found in patients with Opitz BBB/G syndrome (OS), which is characterised by multiple malformations of the ventral midline. MID1 is a microtubule-associated protein that stabilizes microtubules and, in association with the regulatory subunit of protein phosphatase 2A (PP2A), α4, provides ubiquitin ligase activity for the ubiquitin-specific modification of PP2A. Using Fluorescence Recovery After Photobleaching (FRAP) technology, we show here that MID1 is actively and bi-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 36 publications
1
40
0
1
Order By: Relevance
“…␣4 functions as a novel regulatory subunit of protein phosphatase 2A (PP2A), 2 PP4, and PP6 (6 -10). With respect to PP2A, ␣4 binds the catalytic subunit (PP2Ac), at which time it is thought to displace the scaffolding (PP2Aa, PR65) and regulatory subunits (PP2Ab) that typically constitute the PP2A heterotrimeric complex (6,(11)(12)(13). Under growthpromoting conditions, ␣4 down-regulates PP2A activity within the mTOR signaling pathway, resulting in the downstream activation of eIF-4E and S6 kinase and the initiation of cell cycle progression (4,14,15).…”
Section: Alpha4 (␣4) Is a Key Regulator Of Protein Phosphatase 2a (Ppmentioning
confidence: 99%
See 2 more Smart Citations
“…␣4 functions as a novel regulatory subunit of protein phosphatase 2A (PP2A), 2 PP4, and PP6 (6 -10). With respect to PP2A, ␣4 binds the catalytic subunit (PP2Ac), at which time it is thought to displace the scaffolding (PP2Aa, PR65) and regulatory subunits (PP2Ab) that typically constitute the PP2A heterotrimeric complex (6,(11)(12)(13). Under growthpromoting conditions, ␣4 down-regulates PP2A activity within the mTOR signaling pathway, resulting in the downstream activation of eIF-4E and S6 kinase and the initiation of cell cycle progression (4,14,15).…”
Section: Alpha4 (␣4) Is a Key Regulator Of Protein Phosphatase 2a (Ppmentioning
confidence: 99%
“…Given the promiscuity of PP2A, the MID1-␣4-PP2Ac complex likely participates in the regulation of many different cellular processes. For example, this complex has been shown to directly regulate mTORC1 signaling as well as associate with the translational apparatus to regulate translation of various mRNAs including those for MID1 itself (6,8,10,16,26). In each case, it has been concluded that this regulatory role is conferred by MID1-mediated ubiquitination of PP2Ac (6,8,10,28).…”
Section: Alpha4 (␣4) Is a Key Regulator Of Protein Phosphatase 2a (Ppmentioning
confidence: 99%
See 1 more Smart Citation
“…Because OA might induce inhibition of other phosphatases, in addition to PPA2, cells were treated with fostriecin, which has shown specific inhibition of PPA2 at low concentrations. 29 Figure 5B). Taken together, these results suggested that LDL modulate pHSP27 levels via PPA2.…”
Section: Protein Phosphatase A2 Was Involved In Hsp27 Dephosphorylatimentioning
confidence: 95%
“…MID1 is a microtubule-associated E3 ligase that targets the phosphatase PP2A for degradation [3], the microtubule association of MID1 is regulated by phosphorylation [4], active transport of MID1 along microtubules is regulated by PP2A [5], and MID1 localizes specific mRNA molecules to microtubules [6,7]. MID1 indeed is a key player in development and, as briefly described below, also in disease [6].…”
mentioning
confidence: 99%